2020
DOI: 10.1017/s0033291720003128
|View full text |Cite
|
Sign up to set email alerts
|

Development of health care workers' mental health during the SARS-CoV-2 pandemic in Switzerland: two cross-sectional studies

Abstract: Background Virus outbreaks such as the current SARS-CoV-2 pandemic are challenging for health care workers (HCWs), affecting their workload and their mental health. Since both, workload and HCW's well-being are related to the quality of care, continuous monitoring of working hours and indicators of mental health in HCWs is of relevance during the current pandemic. The existing investigations, however, have been limited to a single study period. We examined changes in working hours and mental health in Swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 17 publications
1
33
0
Order By: Relevance
“…Roughly one in three had worked more hours than usual. This finding was confirmatory of Spiller et al (2020) , who further found that hours worked were sluggish in converging back to previous levels. Even before the pandemic, excessive labor of healthcare workers had been an often-discussed topic in the literature, particularly regarding its effect on psycho-social function, productivity, and working errors in an industry, where the margin for error often is small (see e.g., Caruso, 2006 ; Griffiths et al, 2014 ).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Roughly one in three had worked more hours than usual. This finding was confirmatory of Spiller et al (2020) , who further found that hours worked were sluggish in converging back to previous levels. Even before the pandemic, excessive labor of healthcare workers had been an often-discussed topic in the literature, particularly regarding its effect on psycho-social function, productivity, and working errors in an industry, where the margin for error often is small (see e.g., Caruso, 2006 ; Griffiths et al, 2014 ).…”
Section: Discussionsupporting
confidence: 75%
“…Exceptions are given as follows. Spiller et al (2020) , who focused specifically on a sample of Swiss healthcare workers, found no substantial changes in anxiety or depression over the course of the COVID-19 pandemic. Aebischer et al (2020) , who surveyed 227 resident medical doctors and 550 medical students through snowball sampling in Switzerland, found that those medical students who were involved in the COVID-19 response (30%) displayed higher levels of emotional distress than their non-involved peers, and lower levels of burnout compared to the residents.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…These studies have focused on topics such as the initial preparation and first reaction after the outbreak, [20] strategies of contact tracing and isolation as the pandemic evolved, [21] protective equipment for healthcare staff, [22] work risks in the healthcare sector, [23] lockdown measures, [24] governmental policy effectiveness, [25,26] and key lessons to be learned. [27] Nevertheless, our study closes a gap by focusing specifically on healthcare workers/students and their experiences, assessment, and knowledge as a source of quantitative empirical information, while such data is still scarce: Spiller et al [12] found that hours worked by Swiss healthcare workers had increased during the height of the first pandemic wave but afterward did not fully converge back to the levels before the pandemic. Uccella et al [19] found a similar result specific to intensive care in Italy and Switzerland.…”
Section: Literature On Knowledge Risk Perception and Emotional Distmentioning
confidence: 89%
“…Puci et al [11] provided evidence of high perceived risk of getting infected with COVID-19 among Italian healthcare workers, as well as of sleep disturbances (64%) and a high demand for psychological support (84%). Spiller et al [12] assessed anxiety and depression within a sample of Swiss healthcare workers, however found no substantial effects caused by COVID-19. Aebischer et al [13] found increased levels of emotional distress among medical students who were involved in the COVID-19 response.…”
Section: Literature On Knowledge Risk Perception and Emotional Distmentioning
confidence: 99%